Drug-induced AF: Arrhythmogenic Mechanisms and Management Strategies - Bingxun Li; Mingjie Lin; Lin Wu (Arrhythmia & Electrophysiology Review, 2024)
AF is a prevalent condition that is associated with various modifiable and unmodifiable risk factors. Drug-induced AF, despite being commonly under-recognised, can be relatively easy to manage. Numerous cardiovascular and non-cardiovascular agents, including catecholaminergic agents, adenosine, anti-tumour agents and others, have been reported to induce AF. However, the mechanisms underlying drug-induced AF are diverse and not fully understood. The complexity of clinical scenarios and insufficient knowledge regarding drug-induced AF have rendered the management of this condition complicated, and current treatment guidelines follow those for other types of AF. Here, we present a review of the epidemiology of drug-induced AF and highlight a range of drugs that can induce or exacerbate AF, along with their molecular and electrophysiological mechanisms. Given the inadequate evidence and lack of attention, further research is crucial to underscore the clinical significance of drug-induced AF, clarify the underlying mechanisms and develop effective treatment strategies for the condition.